The Surface Plasmon Resonance Effect on the Defect-Mode Cholesteric Liquid Crystals Doped With Gold Nanoparticles - Yu-Sung Liu; Hui-Chi Lin; Han-Lin Xu (IEEE Photonics Journal, 2018)
Cholesteric liquid crystals exhibit the characteristics of photonic crystals with a photonic bandgap. A defect-mode cholesteric liquid crystal module was assembled in this study, and laser dye and gold nanoparticles are mixed into this module. With the help of localized surface plasmon effect induced by the gold nanoparticles, the fluorescence was significantly enhanced at both the band edges and the defect spectrum dip.